2018
DOI: 10.2147/amep.s158784
|View full text |Cite
|
Sign up to set email alerts
|

Matching medical student achievement to learning objectives and outcomes: a paradigm shift for an implemented teaching module

Abstract: IntroductionLow student achievement in a basic imaging module was the impetus for an assessment of the module.MethodsA valid, reliable, and structured Likert scale was designed to measure the degree of student satisfaction with the domains of the module, including learning objectives (LO), teaching strategy and tools (TT), assessment tools (AT), and allotted credit hours (CH). Further analysis was conducted of student dissatisfaction to determine the subdomain in which module improvement was to be implemented.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Researchers also found that SDL can be effectively inculcated in the current curriculum if it is properly framed with desired outcomes at each stage or phase of the curriculum. [33] the new curriculum demands implementation of SDL sessions but there has to be a clari cation in framing the learning objectives, facilitator driven discussions with the learner, by dividing the students in smaller groups encouraging the group discussions by identifying the learning styles of the student. which need to be implemented in order to get the better results.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers also found that SDL can be effectively inculcated in the current curriculum if it is properly framed with desired outcomes at each stage or phase of the curriculum. [33] the new curriculum demands implementation of SDL sessions but there has to be a clari cation in framing the learning objectives, facilitator driven discussions with the learner, by dividing the students in smaller groups encouraging the group discussions by identifying the learning styles of the student. which need to be implemented in order to get the better results.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was composed of both qualitative and quantitative components. The qualitative items were scored on a Likert scale of one to five according to the level of satisfaction (11)(12)(13)(14). In the qualitative component, the respondents were required to write comments about various features of the integrated curriculum in terms of its strengths and limitations.…”
Section: Methodsmentioning
confidence: 99%
“…In response to some of the drawbacks that emerged through an investigative periodic curricular evaluation at different medical schools including Albaha School of Medicine (ABSM) (10)(11)(12)(13), an improvement action plan was created to provide a solution to these limitations. The first step is to identify the major issues that interfere with curriculum implementation especially in the newly integrated medical schools.…”
Section: Introductionmentioning
confidence: 99%
“…• іnstruction -learning the subjects Bioorganic and Biological Chemistry and Medical Biology includes carrying out laboratory-practical works according to the instructions to every practical work with additional element of filling in tables, learning diagrams, supplementing figures and schemes with further writing down into a workbook, that in its turn, trains students to plan their work and organize self-testing of their work, analysis and drawing conclusions [11].…”
Section: роль межпредметной интеграции при изучении дисциплин "биооргmentioning
confidence: 99%